Phylogenetic analysis of Mangifera from central region of Sumatra using trnL-F intergenic spacer - FITMAWATI FITMAWATI; ROSLINA FAUZIAH; IBNA HAYATI; NERY SOFIYANTI; EIICHI INOUE; DEDEN DERAJAT MATRA (Society for Indonesian Biodiversity, 2017)
Fitmawati, Fauziah R, Hayati I, Sofiyanti N, Inoue E, Matra DD. 2017. Phylogenetic analysis of Mangifera from central region of Sumatra using trnL-F intergenic spacer. Biodiversitas 18: 1035-1040. Mangifera from Central Sumatra has an unique ability to adapt to the high rainfall regions. This genus is therefore as a potential germplasm source in Sumatra. The aim of this study was to analyze and compare the nucleotide sequences of Mangifera in the central region of Sumatra based on gene loci of trnL-F intergenic spacer. The initial step of research was conducted by isolating DNA from leaves sample of Mangifera based on CTAB method. Sequences of gene loci of trnL-F were analyzed with Maximum Parsimony and Neighbour Joining methods through PAUP* Program version 4.0b10. From the results of sequences analysis with Maximum Parsimony method, it was obtained a monophyletic group of Mangifera consisted of two main clades which separated M. kemanga from five other species of Mangifera, i.e. M. foetida, M. odorata, M. laurina and Mangifera sp. Parsimony analysis also revealed that the common ancestor of M. kemanga is the first species appeared in the central region of Sumatra. The result of Neighbour Joining analysis showed M. laurina had the longest genetic distance among examined species and might be assumed as the most primitive species of Mangifera. Mangifera laurina and M. odorata were closely related as well as M. foetida and M. odorata. The results of research also revealed and supported the genus Mangifera as a monophyletic group.